Effects of water and exogenous Si on element concentrations and ecological stoichiometry of plantain (Plantago lanceolata L.). (15th June 2018) - Long, Mingxiu; Guo, Lixiang; Li, Jing; Yu, Cui; Hu, Tianming; Yue, Jiaming; He, Shubin
ABSTRACT: Silicon (Si) is widely distributed in nature and can promote plant growth under various biotic and abiotic stresses. Drought stress seriously affects plant growth and the concentration and ecological stoichiometry of nutrients. Integrated nutrient management effectively protects plants from stresses. However, the role of water and Si availability on element concentrations and stoichiometry in plantain ( Plantago lanceolata L.) are unclear. Accordingly, this study observed changes in the concentration and stoichiometry of macro- and micro-elements in plantain leaves supplied with various levels of Si under variable water availabilities through a greenhouse experiment. Supplemental Si increased Si concentration of leaves under both well-watered and drought conditions. Without supplemental Si, drought conditions decreased concentrations of carbon (C), C: nitrogen (N), C: phosphorus (P), silicon (Si):N, Si:P and increased concentrations of N, P, N:P, Si:C, calcium (Ca 2+ ), magnesium (Mg 2+ ), iron (Fe), manganese (Mn), zinc (Zn), and copper (Cu). Increased Si under water stress increased concentrations of C, C:N, C:P, Si:C, Si:N, and Si:P, and decreased concentrations of Ca 2+, sodium (Na + ), and Mg 2+ . These results suggested that exogenous Si changed the concentrations and ecological stoichiometry of macro- and micro-elements.